On the use of ultra-high resolution PIC methods to unveil microscale effects of plasma kinetic instabilities: electron trapping and release by electrostatic tidal effect. (1st April 2022) - Schiesko, L; Revel, A; Minea, T; Carbone, E
Abstract: Ultra-high resolution particle-in-cell coupled to Monte-Carlo collisions modelling unveils microscale instabilities in non-equilibrium plasmas fulfilling Penrose's instability criterion. The spontaneous development of ion turbulence in the phase-space generated by charge exchange collisions leads to finite amplitude modulations of the local electric field. The latter are responsible for the trapping of low energy electrons and their transport from the plasma volume to the sheath vicinity. Electrostatic tidal effect occurring near the sheath is responsible for the release of the trapped electrons as a monochromatic bunch, accelerated back towards the source. This instability provides an additional theoretical ground for the anomalous enrichment of low-energy electrons observed by Langmuir probes in similar conditions. The present results demonstrate that marginally fulfilling PIC criteria is insufficient to study the microscale instabilities effects on the electrons dynamics in non-equilibrium low temperature plasmas.